2018
DOI: 10.1021/acs.jpcc.8b06739
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study on the Single Ir Atom Embedded Graphdiyne: An Efficient Catalyst for CO Oxidation

Abstract: Single-atom catalysts have attracted wide attention due to the maximum usage of single atom and the great potential to achieve high activity and selectivity. The oxidation of CO molecules on the single Ir atom embedded graphdiyne (Ir-GDY) has been investigated by using the first-principles calculations. A variety of reaction mechanisms are taken into account and a new pathway is found to catalyze CO oxidation more efficiently on Ir-GDY. A comparison of the reaction energy barrier shows that the CO oxidation li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 51 publications
1
46
0
Order By: Relevance
“…Lu et al found that single Ir atom-embedded graphdiyne can catalyze CO oxidation more efficiently through the NER mechanism with the activation energy of 0.37 eV. 47 Keke Mao et al found that a h-BN monolayer fixed single gold atom catalyzed CO preferring the TER reaction with an energy barrier of 0.47 eV. 48 Next, we comprehensively analyze the four oxidation mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Lu et al found that single Ir atom-embedded graphdiyne can catalyze CO oxidation more efficiently through the NER mechanism with the activation energy of 0.37 eV. 47 Keke Mao et al found that a h-BN monolayer fixed single gold atom catalyzed CO preferring the TER reaction with an energy barrier of 0.47 eV. 48 Next, we comprehensively analyze the four oxidation mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the current research focusing on biomedical applications of SACs mainly concentrates on cancer treatment, wound disinfection, biosensing, and oxidative‐stress cytoprotection, while other biomedical applications including diagnosis, multimodal imaging, inflammation alleviation as well as Alzheimer's disease, Parkinson's disease, and diabetes treatment are rarely studied. In addition, although numerous SACs have been successfully fabricated, including diverse single metal atoms (Au, Co, Fe, Ir, Ru, Pt, Pd, etc.) on various supports such as N‐doped carbon, metal oxides, and layered double hydroxides, only Fe‐, Au‐, Zn‐, and Cu‐based SACs, especially M‐N‐C nanostructures, have been demonstrated their potential in biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…DFT-based studies showed that Ir 1 /graphdiyne preferentially follows the TER mechanism in which O 2 bridges with two adsorbed CO molecules, forming two CO 2 molecules. [66] In summary, the catalytic performance and reaction mechanisms of Rh/Ir SACs are highly affected by their supports. MvK, ER, and TER mechanisms were reported on different supports.…”
Section: Rh and Ir Sacsmentioning
confidence: 99%